The Role of Technology in Effective Managerial Decision-Making in a Dynamic Business Environment: An Empirical Study - S. Baskaran (Journal of Informatics Education and Research, 2024)
Efficiency, agility, and accuracy within a dynamic business environment are enhanced by the use of technology plays a vital role in effective managerial decision-making. Actionable insights and predictive capabilities, supporting data-driven strategies are all provided by Advanced data analytics and AI to the managers. Real-time information systems and communication tools facilitate swift coordination and informed responses. Risk management is also offered by Technology through advanced monitoring, risk assessment, and crisis management solutions. In terms of resource management, automation, ERP systems, and workforce management tools streamline operations and optimize resource use. Managers are overall empowered by technology to make timely, informed, and adaptive decisions to stay competitive and resilient. A sample of 211 people from different business sectors were surveyed to know the factors that determine different Roles of Technology in Effective Managerial Decision-making in the Dynamically Business Environment and found that Data-Driven Insights, Automation and AI, Risk Management, and Efficient Resource Management are different factors showing Role of Technology in Effective Managerial Decision Making.